2017
DOI: 10.1101/184002
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polysaccharide-mediated synthesis of melanins from serotonin and other 5-hydroxy indoles

Abstract: As a continuation of our research on the melanin formation from catecholamines, we studied the polysaccharidemediated oxidation of serotonin and other 5-hydroxy indoles into melanin-like materials. As for the catecholamines, we observed that many polysaccharides promote the oxidation of such compounds, particularly in the presence of Cu 2+. The reactions were monitored using RP-HPLC and SEC techniques. Melanin-like materials were purified through dialysis and evaluated using UV_Vis and FT_IR spectroscopic tech… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…This report expands our earlier observations on the formation of MN-like pigments from a wide variety of catecholic or indolic precursors. [16][17][18][19][20][21]23] The chemical processes used to generate these MN-like pigments are non-enzymatic, using air-mediated (in the presence of PS or alkaline solutions) or Fe 2+ /H 2 O 2 -mediated oxidation. Strong alkaline solutions are very effective in converting catecholic precursors like L-DOPA (this report), homogentisic acid [23], catechol or pyrogallol [17] into darkcolored, MN-like pigments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This report expands our earlier observations on the formation of MN-like pigments from a wide variety of catecholic or indolic precursors. [16][17][18][19][20][21]23] The chemical processes used to generate these MN-like pigments are non-enzymatic, using air-mediated (in the presence of PS or alkaline solutions) or Fe 2+ /H 2 O 2 -mediated oxidation. Strong alkaline solutions are very effective in converting catecholic precursors like L-DOPA (this report), homogentisic acid [23], catechol or pyrogallol [17] into darkcolored, MN-like pigments.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] In previous reports we have presented our observations regarding the synthesis of MN-like pigments from a multitude of precursors using polysaccharides (PS) or a combination of Fe 2+ and H 2 O 2 . [16][17][18][19][20][21] We observed that many PS can promote the formation of MN-like pigments using different types of precursors leading to darkly colored solutions or materials. Despite the obvious presence of a darkly-colored pigment, the PS/pigment complexes tended to contain mostly PS material with very little pigment bonded to it as judged from FT-IR analyses.…”
Section: Introductionmentioning
confidence: 93%
“…[28][29][30] In recent years we have presented various studies on the air-or reactive oxygen species-mediated oxidation of various catecholic compounds into dark-or light-colored pigments. [31][32][33][34][35][36][37][38] This report presents our first attempt to generate pheomelanin-like pigments by including L-cysteine into the reaction mixtures. As before, we evaluated our reactions through UV-Vis spectroscopic measurements and size exclusion chromatography (SEC) analyses.…”
Section: Scheme 1: Basic Outline Of the Biosynthesis Of Eumelanin Andmentioning
confidence: 99%
“…The value of SEC analysis to monitor the formation of colored pigments from catecholic or phenolic compounds has been discussed in previous reports. [9][10][11][12][13]26 In SEC, molecules are separated on the basis of differences in their hydrodynamic volume (often related to the molecular mass of the molecule): the lower the retention time, the higher the hydrodynamic volume of the analyte. In our SEC analyses, the lower limit of exclusion, as determined by the injection of water, was about 15 minutes.…”
Section: Fig3: Effect Of H2o2 On Color Formation and Reactivity For mentioning
confidence: 99%
“…Some of these compounds have been the subject of previous studies on the formation of MN-like pigments performed in our laboratories. [9][10][11][12][13] In biological samples, the MN pigments may present themselves as particulate matter of different sizes and shapes. The physic-chemical properties of MN particles, e.g., aggregation, have been studied and reviewed extensively before.…”
Section: Introductionmentioning
confidence: 99%